Pulmonary arteriovenous malformation: Case report - Sekulić Igor; Sagić Dragan; Rusović Siniša; Dulović Dragan; Pasovski Viktor; Bošković-Sekulić Jelena; Rančić Nemanja; Stevanović Jelena; Raičević Ranko (Vojnosanitetski Pregled)
Introduction. Pulmonary arteriovenous malformation (PAVM) is pathological communication between pulmonary artery and pulmonary vein, in way that it shunts normal alveolar capillary membrane resulting in inadequate blood oxygenation in this part of the lung parenchyma Modern therapy of PAVMs includes surgical treatment or endovascular embolization. Case report. A 30-year-old female patient had signs of parestesia and weakness of the extremities on the left side of her body. On physical examination there was only cyanotic discoloration of her lips and clubbing fingers. On the chest x-ray, in the right hemithorax, in the inferior region of the lung, there was relatively homogeneous and well defined shadow, intensity of the soft tissue, which was about 35 mm. A multislice computed tomography pulmonary angiography was performed and showed, in lung parenchyma on both sides, many PAVMs, of which the largest (35 mm) was in inferior right region of the lung on crossing between apical and posterior basal lung segment with 7 mm diameter feeding artery and 9 mm diameter draining vein. The selective pulmonary angiography was per-formed by Seldingers technique. Through sheath, we placed a plug with a diameter of 10 mm. The plug was expanded and a complete occlusion of the final part of the feeding branch of this PAVM was achieved (confirmed by control angiography). In that way, the PAVM was fully shut off from the circulation. In 3 months follow-up, the patient was feeling well, without any recorded complication. Conclusion. Endovascular embolization is recommended as therapy of the first choice for all of PAVMs that have feeding artery greater than 2 mm. Endovascular embolization has high success rate with minimal complications.